2018
DOI: 10.2110/jsr.2018.58
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Controls On the Development of Contemporaneous but Contrasting Basin-Floor Depositional Architectures

Abstract: This is a repository copy of Topographic controls on the development of contemporaneous but contrasting basin-floor depositional architectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 133 publications
(311 reference statements)
0
61
0
Order By: Relevance
“…Beautiful examples of this are shown from the Marnoso‐arenacea, Italy, where grooves show an enhanced variability relative to flutes, which is interpreted to be a result of topographic interaction (Muzzi Magalhaes & Tinterri, , fig. 20; Tinterri & Muzzi Magalhaes, ; Bell et al., ). However, in other examples of interaction with topography, flutes and grooves show similar palaeocurrents (Tinterri et al., ; Cunha et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Beautiful examples of this are shown from the Marnoso‐arenacea, Italy, where grooves show an enhanced variability relative to flutes, which is interpreted to be a result of topographic interaction (Muzzi Magalhaes & Tinterri, , fig. 20; Tinterri & Muzzi Magalhaes, ; Bell et al., ). However, in other examples of interaction with topography, flutes and grooves show similar palaeocurrents (Tinterri et al., ; Cunha et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Confined basins have previously been associated with sheet-like deposition, where incoming flows are entirely confined by the basin margins, resulting in tabular stratigraphy with little or no autogenic compensational stacking (e.g., Sinclair and Tomasso, 2002). Numerical studies (Dorrell et al 2018), subsurface studies (e.g., Beaubouef and Friedmann, 2000), and outcrop studies (e.g., Spychala et al 2016;Bell et al 2018b;Liu et al 2018), however, have shown the stacking-pattern complexity that may arise in basins that display variable degrees of confinement. This study uses data from the lowermost member of the Grès d'Annot, the Le Ray member (Figs 5, 6), to build on these studies.…”
Section: Le Raymentioning
confidence: 99%
“…Recent field-based studies on the spatial and temporal evolution of unconfined submarine lobes have used the longitudinal evolution of flows and their associated facies to establish criteria for differentiating lobe sub-environments at the bed scale (e.g., Prélat et al 2009;Grundvag et al 2014;Spychala et al 2017). The applicability of these facies associations to confined lobes and the complex system-scale stacking patterns that they may produce is only recently being investigated (e.g., Marini et al 2015;Spychala et al 2015Spychala et al , 2017Bell et al 2018b;Fonnesu et al 2018;Liu et al 2018). Previous flowdependant onlap models mainly focussed on end-member geometries (e.g., McCaffrey and Kneller, 2001;Smith, 2004b;Smith and Joseph, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some outcrops have a narrow palaeocurrent dispersal pattern (e.g. In addition, a number of palaeocurrent measurements have a southerly component, opposite to the regional trend, which could indicate flow reflection and deflection from local topography (Potter and Pettijohn, 1977;Kneller et al, 1991;Lomas and Joseph, 2004;Bell et al, 2018). Others have multiple palaeocurrent directions between beds (e.g.…”
Section: Fa 4a: Deep Water Bottomsetsmentioning
confidence: 99%
“…Locality X, Figure 6) implying both Kerinitis and Selinous fan delta sources ( Figure 6). In addition, a number of palaeocurrent measurements have a southerly component, opposite to the regional trend, which could indicate flow reflection and deflection from local topography (Potter and Pettijohn, 1977;Kneller et al, 1991;Lomas and Joseph, 2004;Bell et al, 2018). Barrett et al (2019) previously classified the shallow water bottomset (FA 4b) as coarse (sand to gravel-grade) sediments with multiple and diverse sedimentary structures, such as symmetrical and asymmetrical ripple laminations, wavy and planar laminations, dune-scale gravel cross-beds and soft-sediment deformation, indicating sediment gravity flows and wave reworking operating at the base of slope in shallow water.…”
Section: Fa 4a: Deep Water Bottomsetsmentioning
confidence: 99%